2015
DOI: 10.1063/1.4921729
|View full text |Cite
|
Sign up to set email alerts
|

Brownian motion of a particle with arbitrary shape

Abstract: Brownian motion of a particle with an arbitrary shape is investigated theoretically. Analytical expressions for the time-dependent cross-correlations of the Brownian translational and rotational displacements are derived from the Smoluchowski equation. The role of the particle mobility center is determined and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Finally, let us briefly recall the case of a rigid macromolecule. In such a case, the memory function can be calculated analytically (Cichocki, Ekiel-Jezewska & Wajnryb 2012; Cichocki, Ekiel-Jeżewska & Wajnryb 2015) and it can be shown that there exists a reference point for which the memory function vanishes; thus the mean square displacement of this point is linear over the entire time range.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, let us briefly recall the case of a rigid macromolecule. In such a case, the memory function can be calculated analytically (Cichocki, Ekiel-Jezewska & Wajnryb 2012; Cichocki, Ekiel-Jeżewska & Wajnryb 2015) and it can be shown that there exists a reference point for which the memory function vanishes; thus the mean square displacement of this point is linear over the entire time range.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mo et al [16] studied the Brownian motion of a sphere in the vicinity of a plane wall, showing the effect of wettability on the statistical properties of particle motion. Cichocki et al [17] performed a theoretical analysis of the Brownian motion of a particle with an arbitrary shape. They [17] derived analytical expressions for the time-dependent cross-correlations of the Brownian translational and rotational displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Cichocki et al [17] performed a theoretical analysis of the Brownian motion of a particle with an arbitrary shape. They [17] derived analytical expressions for the time-dependent cross-correlations of the Brownian translational and rotational displacements. Jahanshahi et al [18] studied the dynamics of a Brownian circle swimmer in an external harmonic potential and found a resonance situation for the maximum escape distance as a function of the various frequencies in the system.…”
Section: Introductionmentioning
confidence: 99%
“…For microparticles of complex shapes, a more general theoretical approach is needed to account for the time-dependent Brownian translational and rotational displacements and their cross-correlations. Such an approach has been recently developed, and new analytical expressions have been derived from the Smoluchowski equation for the Brownian motion of a particle with an arbitrary shape [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it seems useful to demonstrate explicitly how to apply the theoretical scheme from Refs. [3,4] to analyze the data from measurements. In this work, we use the interesting experiment from Ref.…”
Section: Introductionmentioning
confidence: 99%